Working Memory Alterations Plays an Essential Role in Developing Global Neuropsychological Impairment in Duchenne Muscular Dystrophy - Tyagi, Rahul; Arvind, Harshita; Goyal, Manoj; Anand, Akshay; Mohanty, Manju (Frontiers in Psychology, 2021)
Background: Neuropsychological profile of Indian DMD subjects remains unidentified and needs to be evaluated. Methods: A total of 69 DMD and 66 controls were subjected to detailed intelligence and neuropsychological assessment. The factor indexes were derived from various components of Malins intelligence for Indian Children (MISIC) and Rey Auditory Verbal Learning Test (RAVLT). Results: Poor verbal and visual memory profiles were demonstrated by DMDs which include RAVLT-Immediate Recall (IR) (p=0.042), RAVLT-Delayed Recall (DR) (p=0.009), Rey–Osterrieth complex figure Test (RCFT)-IR (p=0.001) and RCFT-DR (p=0.001). RAVLT-memory efficiency index demonstrated poor verbal memory efficiency (p=0.008). Significant differences in the functioning of working memory axis [RAVLT T1 (p=0.015), recency T1 (p=0.004), Digit span backward (p=0.103)] was observed along with reduced performance in visuomotor coordination, visuospatial and visual recognition abilities. Block designing efficiency index and Attention fraction showed a normal performance in DMD kids. Conclusion: Working memory deficits were found to be the crucial element of cognitive functioning in DMD cases. Working memory interventions may be beneficial to improve the neuropsychological profile in DMD.